Formulasi Tabir Surya Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) dan Seng Oksida - Barikah, Kuni Zu''Aimah; Wisudyaningsih, Budipratiwi; Nur Fitriana, Mahmudah (Faculty of Pharmacy, University of Jember, 2026)
UV rays can cause several risks such as premature aging, erythema and skin cancer when exposed too long to the skin. Based on this condition, sunscreen product urgently needed to provide maximal protection to the skin. Red dragon (Hylocereus polyrhizus) fruit peel extract has a flavonoid component that potential used as UV chemical blocker for sunscreen product. This study conducted to determine effectiveness of red dragon fruit peel extract when formulated as cream-based sunscreen using zinc oxide as UV physical blocker to optimize the effect. Cream-based sunscreen product formulated with oil-in-water system, with different concentrations of the red dragon fruit peel extract. The final characteristic of the cream was determined using the pH value, viscosity and spreadability, Sun Protection Factor (SPF) value, % Transmission of Erythema (%TE) value and % Transmission of Pigmentation (%TP) value. All the cream preparation successfully met the physical characteristics (pH, viscosity, and spreadibility) that previously determined. Cream with the 14 % extract concentration (F3) has the highest sunscreen effectivity determined by highest SPF value (15.57 ± 1.32), and lowest % TE value (0.88 ± 0.36) and % TP value (2.68 ± 0.10) (p<0,05). According to result, red dragon fruit peel extract has a great potential activity to develop into sunscreen product. Cream-based sunscreen using the extract able to produce ultra and total block protection based on SPF, % TE and % TP value.